Temperature effect on the sensitivity of the copepod Eucyclops serrulatus (crustacea, copepoda, cyclopoida) to agricultural pollutants in the hyporheic zone - di Lorenzo, Tiziana (2015)
The sensitivity of freshwater invertebrates to agricultural pollutants is supposed to increase with rising temperature due to global warming. The aim of this study was to measure the effect of temperature on the lethal toxicity of ammonia-N, the herbicide Imazamox and the mixture of the two chemicals, in the adults and the juveniles of a population of the copepod Eucyclops serrulatus. This is a widely distributed species found in surface waters, in transitional habitats between surface water and groundwater, and in genuine groundwater environments. We tested the sensitivity by short-term bioassays (96 h) at 15°C and 18°C, respectively. Our results highlighted the following: (1) increasing temperature affected the sensitivity of the adults to ammonia-N and of the juveniles to the mixture, all of which were more sensitive to its detrimental effects at 18°C; (2) the juvenile stages were more sensitive than the adults to all toxicants, and (3) for all combinations of chemicals and temperatures, the effects were synergistic and approximately one order of magnitude greater than those expected according to a concentration addition model when comparing the LC50 for each chemical in the mixture with the LC50s of chemicals individually assayed. Overall, in a context of global change, ammonia-N and mixtures of agricultural pollutants may affect the survival rate of species that spend a part or the whole life-cycle in the hyporheic habitat, with detrimental effects to biodiversity and ecosystem services provided by the hyporheic biota.